Local Wisdom-Based Education Management: Building Identity in the Midst of Globalization - Haetami Haetami (Gestion Educativa, 2024)
Globalization has a significant impact on various aspects of life, including education. The rapid flow of globalization often makes the education system tend to follow international standards and forget local values ​​that are part of a nation's cultural identity. In the context of Indonesia, which is rich in cultural diversity, local wisdom-based education management is important to maintain and strengthen national identity. Education that integrates local wisdom not only serves to preserve culture, but also to shape the character of the younger generation who have insight and deep understanding of the noble values ​​of their culture. This study aims to examine the importance of local wisdom-based education management in building identity amidst the challenges of globalization. The approach used in this study is qualitative with a literature study method, to analyze the relevance and application of local wisdom in the education system in Indonesia. The results of the study show that the application of local wisdom-based education can strengthen a sense of pride in indigenous culture and form individuals who are more sensitive to diversity. Although there are challenges in integrating local wisdom-based curriculum, the great potential to keep national identity relevant and strong amidst the influence of globalization is very open.